2018
DOI: 10.1097/md.0000000000009644
|View full text |Cite
|
Sign up to set email alerts
|

Acute lymphoblastic leukemia arising after treatment of Ewing sarcoma was misdiagnosed as bone marrow metastasis of Ewing sarcoma

Abstract: Rationale:Both acute lymphoblastic leukemia (ALL) and Ewing sarcoma (ES) are small round cell tumors, and it is difficult to differential diagnose them because of overlapping clinical, radiographic, histologic, and immunophenotypic features.Patient's concerns:A 5-year-old boy was admitted to our hospital because of pains in his left leg without obvious inducement and lameness worsening with walking over a two 2-month period.Diagnoses:Based on the comprehensive analysis of radiography, magnetic resonance imagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…From a morphological point of view, histopathological diagnosis of EwS has been notoriously difficult due to its highly undifferentiated small-round-cell phenotype being shared with a variety of differential diagnoses [19], such as neuroblastoma, rhabdomyosarcoma, lymphoblastic lymphoma, desmoplastic small round cell tumor (DSRCT), and round-cell liposarcoma [20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…From a morphological point of view, histopathological diagnosis of EwS has been notoriously difficult due to its highly undifferentiated small-round-cell phenotype being shared with a variety of differential diagnoses [19], such as neuroblastoma, rhabdomyosarcoma, lymphoblastic lymphoma, desmoplastic small round cell tumor (DSRCT), and round-cell liposarcoma [20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Bhatia et al confirmed that the risk of AML and MDS increased during treatments with a combination of anthracyclines (doxorubicin) and alkylating agents (cyclophosphamide, ifosfamide), as well as an increased cumulative dose of ifosfamide, cyclophosphamide, and doxorubicin [ 18 ]. Although there are several case reports of the association between chemotherapy and SMNs, few studies such as Bhatia et al’s study have demonstrated a significant association between SMNs and the use of the latter chemotherapeutic agents [ 18 , 62 ]. It is also known that the use of G-CSF in combination with etoposide increases the risk of secondary leukemia [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] Radiographic evaluation of ES shows permeative and infiltrative destruction of the involved bone, accompanied by periosteal reaction, such as onion skin appearance and codman triangle, or calcified spicule. 11 In the primary vertebral ES, the division of the spine into non-sacral (cervical, dorsal, and lumbar) and sacral (sacral and coccygeal) is important because sacral ES is considered aggressive and less responsive to therapy. 2,12 On the same note, the primary non-sacral ES occurs in 0.9% of all cases.…”
mentioning
confidence: 99%